VIRAL MUSICKING: AESTHETICS AND ITERATIONS IN ONLINE CONTAGION - Harper, Paula Clare (AoIR Selected Papers of Internet Research, 2020)
Cats at keyboards. Dancing hamsters. A photo of a dress, and videos set to “Harlem Shake.” The above are recognizable as “viral” phenomena—artifacts of the early twenty-first century whose production and dissemination were facilitated by the internet, proliferating social media platforms, and ubiquitous digital devices. In this paper, I argue that participation in such phenomena (producing, consuming, circulating, or “sharing” them) constitutes a significant site of twenty-first-century musical practice: viral musicking, to borrow and adapt Christopher Small’s foundational 1998 coinage. In this paper I analyze instances of viral musicking from the 2000s through the 2010s, tracking viral circulation as heterogeneous, capacious, and contradictory—a dynamic, relational assemblage of both “new” and “old” media and practices. The notion of virus as a metaphor for cultural spread is often credited to computer science and science fiction, with subsequent co-option into marketing and media; such formulations run adjacent to the popularization of "virus" in philosophical models for globalization and pervasive capitalism across the late twentieth century, from Derrida to Baudrillard and Deleuze. In this paper, I seek to braid these lineages with the work of scholars reading cultural contagion through lenses of alterity and difference, situating music as a particularly felicitous vector for viral contagion, exceeding and preceding Internet circulation. Ultimately, I argue that viral musicking activates utopian promises of digital advocates, through the cooperative social operation of “sharing,” even as it resonates through histories and presents of racialization, miscegenation, appropriation, and the realities of porous, breachable borders, cultures, and bodies.